Student Perception of Task-Based language Teaching In Learning Vocabulary At Universitas Bumigora - Hilda Hastuti; Lela Rahmawati; Ni Ketut Putri Nila Sudewi (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This study aims to describe student perceptions of the task learning process for Vocabulary subjects at Universitas Bumigora This research is a qualitative research with descriptive research type. Primary data sources that are the subject of research are students, as well as secondary data sources obtained from the internet or books. Techniques in data collection is done by observation and mediated interview. The results of the study show that the perceptions of students in the implementation of task-based learning on vocabulary subjects are satisfactory, effective and efficient from the students themselves. This is because task-based learning encourages self-directed rather than teacher-directed learning, encourage students to participate actively, and build intrinsic rather than extrinsic motivation.